2013
DOI: 10.1002/anie.201300464
|View full text |Cite
|
Sign up to set email alerts
|

A Catenane Assembled through a Single Charge‐Assisted Halogen Bond

Abstract: Getting connected: The formation of pseudorotaxane assemblies between a designed macrocyclic halogen bonding (XB) acceptor (red in scheme) and a series of XB donor threading components was templated by a single halogen bond. The strength of the XB assembly between the pyridine macrocycle and iodopyridinium thread was utilized in the ring‐closing metathesis clipping synthesis of a [2]catenane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 36 publications
0
52
0
3
Order By: Relevance
“…Halogen bond [1], a noncovalent interaction between an electron donor and a covalently bonded halogen atom acting as an electron acceptor, has attracted an increasing attention recently [2][3][4][5][6][7][8], because it can act as a molecular linker in molecular recognition [9][10][11], and material science [12][13][14]. Similar with hydrogen bond, halogen bond also exhibits the cooperative effect, which is responsible for its potential applications in crystal structures and supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Halogen bond [1], a noncovalent interaction between an electron donor and a covalently bonded halogen atom acting as an electron acceptor, has attracted an increasing attention recently [2][3][4][5][6][7][8], because it can act as a molecular linker in molecular recognition [9][10][11], and material science [12][13][14]. Similar with hydrogen bond, halogen bond also exhibits the cooperative effect, which is responsible for its potential applications in crystal structures and supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] XBs can be applied, among other fields,i ns upramolecular chemistry [9,10] or anion recognition in solution. [14][15][16][17][18][19][20] In particular,t he interaction of 2-halofunctionalized imidazolium motifs with halide anionst hrough XBs has found several applications,f or instance, in the chloride-templated assembly of ap seudorotaxane in CHCl 3 , [14] taking advantage of the existence of cooperative halogen (CÀ Br···Cl À )a nd hydrogen (NÀH···Cl À )b onds (Scheme1a). [14][15][16][17][18][19][20] In particular,t he interaction of 2-halofunctionalized imidazolium motifs with halide anionst hrough XBs has found several applications,f or instance, in the chloride-templated assembly of ap seudorotaxane in CHCl 3 , [14] taking advantage of the existence of cooperative halogen (CÀ Br···Cl À )a nd hydrogen (NÀH···Cl À )b onds (Scheme1a).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that many properties of the halogen bond are analogous to those of the hydrogen bond [12][13][14]. For example, concerning strength, halogen bonds are comparable to hydrogen bonds and thus a competition may occur between them, thus in recent years much attention has been paid to it [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%